A REFINEMENT ON THE GROWTH FACTOR IN GAUSSIAN ELIMINATION FOR ACCRETIVE-DISSIPATIVE MATRICES - Yang, Junjian (Italian Journal of Pure and Applied Mathematics, 2014)
In this note, we give a refinement of the growth factor in Gaussian elimination for accretive-dissipative matrix A which is due to Lin [Calcolo, 2013, DOI 10.1007/s10092-013-0089-1].